Pengaruh Corporate Social Responsibility, Good Corporate Governance dan Profitabilitas Terhadap Nilai Perusahaan Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Doaly, Deutmar Londo; Herlambang, Herlambang; Yusuf, Yusuf (Prisani Cendekia, 2025)
This study aims to analyze the effect of Corporate Social Responsibility, Good Corporate Governance, and profitability on firm value with firm size as a moderating variable in the banking sector listed on the Indonesia Stock Exchange. The data used are secondary data obtained from annual reports and sustainability reports of the companies during the research period. The analytical method employed is moderated regression analysis to examine the role of firm size in strengthening or weakening the relationships among variables. The results indicate that Corporate Social Responsibility has a negative but insignificant effect on firm value, Good Corporate Governance has a significant negative effect, while profitability exerts a positive yet insignificant effect. Firm size is proven to partially moderate the relationship between the independent variables and firm value. These findings imply that banking management needs to optimize governance practices and the disclosure of social responsibility in order to enhance firm value.